Curriculum for Knowledge Base Retrieval Systems:A Case for Inclusion in Information Science - Gopinath, M. A. (Journal of Information and Knowledge, 1991)
The developments in various processing stages of information systems and expert systems are delineated. The knowledge and skill needed in developing an expert system as an information system and the vice-versa are discussed. A curriculum for a course on Intelligent Knowledge Base System is presented.